Emotional vampires : dealing with people who drain you dry - Bernstein, Albert J. (McGraw Hill-Ascent Audio, 2014)
Protect yourself from people who take undue advantage and suck the energy out of your life Emotional Vampires will help you cope effectively with the people in your life that confound you, confuse you, and seem to sap every ounce of your energy. Bestselling author Dr. Al Bernstein shows you how to recognize each vampire type--antisocial, histrionic, narcissists, obsessive-compulsives, paranoids--and deal with them effectively. He uses many examples from the latest news headlines, which will help you distinguish between the types and deepen your understanding of each one. In response to the daily calls and emails he got about the previous edition of this book, Dr. Al Bernstein has added his advice for dealing with those emotional vampires who come in the shape of spouses and lovers, relatives, and children. Dr. Bernstein shows you how to deal with each vampire type and what you need to do to keep from getting drained.